Perubahan Sosial Ekonomi Petambak Udang Mandiri di Desa Bumi Dipasena Mulya Kecamatan Rawajitu Timur Lampung - Aulia Triana Oktavia; Isyanawulan, Gita (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2024)
This research aims to understand the nature and impact of socio-economic changes on independent shrimp farmers in Bumi Dipasena Mulya Village, Rawajitu Timur District, Lampung. The study employs a descriptive qualitative research method. Data collection techniques include observation, interviews, and documentation. The findings indicate that socio-economic factors influence the changes experienced by independent shrimp farmers. These changes are reflected in shifts in social interactions, mindsets, and income levels within the community. These transformations affect how shrimp farmers interact, ultimately impacting the community's environment.